La administración de riesgos y su incidencia en la gestión del activo fijo de la empresa B.Braun Medical Perú S.A. de la ciudad de Lima - período 2015 - Flores Tarrillo, Rut Dianeli (2017)
This research was developed around the implementation of Risk Management in the company B. Braun Medical Peru SA, the problem is how Risk Management impact in the Fixed Assets Management Company B. Braun Medical SA of Peru Lima-period 2015, our main objective was to determine the incidence of Risk management in Fixed Assets management Company in question. The research was descriptive, non-experimental design, and as a population the Company B. Braun Medical Peru S.A. Through the investigation, it was concluded that the Risk Management allows managing its fixed assets that leads to a clear, transparent administration with optimal monitoring of the assets. As main benefits, avoid accounting impact by depreciating assets that no longer exist, comply with internal or external audit requirements, avoid unnecessary purchases of equipment that the company already has and optimize resources and time in the verification of assets, either in cyclical inventories Or newspapers.